Integration of Customer Needs in Sativa Mouthwash Design With Quality Function Development (QFD) Approach - Lusi Zafriana; Ernie Maduratna Setiawatie (Rekayasa, 2023)
Public awareness of oral-hygiene and health has influenced the increase demand for mouthwash products. To support the green innovation program, a mouthwash made from herbs and halal is needed. Sativa mouthwash is an innovative product using 3% Nigella Sativa extract. The QFD method is used as an evaluation of the productivity of Sativa mouthwash through the preparation of the HoQ matrix. It shows the level of connectedness between Customer and Technical Importance to get priority on the main technical interests that must be carried out immediately by the production company. The results of HoQ matrix calculation shows the highest-ranking attributes of the product is Nigella Sativa content, Raw Material Management, and Halal Label Design. The technical priority to achieve the customer interest attributes is packaging type. This means that the attributes of adding and processing Nigella Sativa ingredients that are right and labelled as halal have unique characteristics that greatly affect the sales productivity of Sativa Mouth Wash products. However, on the attribute of the type of packaging, Sativa Mouth Wash has not yet produced in sachets or small bottles which provide convenience and practicality that is needed by the customers